The Mediating Role of Lifestyle in Strengthening Financial Management Behavior of Gen Z - Ramadhani, Indri Gayatri; Aisyah, Siti; Daulay, Aqwa Naser (International Ecsis Association, 2025)
The rapid evolution of digital technology has profoundly shaped the consumption patterns and financial behaviors of Generation Z, a cohort characterized by high digital exposure and instant access to financial services. Despite their familiarity with financial information, many Gen Z individuals still exhibit impulsive spending and poor debt management, reflecting a gap between financial awareness and behavioral discipline. This study aims to examine the influence of financial knowledge and financial attitude on financial management behavior, with lifestyle serving as a mediating variable. Employing a quantitative research design, data were collected from 410 Gen Z students in Medan through an online questionnaire and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The findings reveal that both financial knowledge and financial attitude have significant positive effects on financial management behavior, both directly and indirectly through lifestyle. Furthermore, lifestyle demonstrates a partial mediating role, indicating that sound financial knowledge and positive attitudes are more effective when internalized into disciplined and goal-oriented financial lifestyles. This study contributes to the theoretical enrichment of the Theory of Planned Behavior by emphasizing the mediating role of lifestyle as a behavioral mechanism linking cognition and attitude to practical financial management. Practically, the results highlight the importance of promoting financial education programs that integrate lifestyle adjustments to foster responsible and sustainable financial behavior among the younger generation.